2017
DOI: 10.3390/ijms18010095
|View full text |Cite
|
Sign up to set email alerts
|

Sailuotong Prevents Hydrogen Peroxide (H2O2)-Induced Injury in EA.hy926 Cells

Abstract: Sailuotong (SLT) is a standardised three-herb formulation consisting of Panax ginseng, Ginkgo biloba, and Crocus sativus designed for the management of vascular dementia. While the latest clinical trials have demonstrated beneficial effects of SLT in vascular dementia, the underlying cellular mechanisms have not been fully explored. The aim of this study was to assess the ability and mechanisms of SLT to act against hydrogen peroxide (H2O2)-induced oxidative damage in cultured human vascular endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Generally, the ratio of Bax to Bcl-2 is used to evaluate the degree of apoptosis. When the ratio increases, and apoptosis will be aggravated [ 57 ]. The results revealed that H 2 O 2 increased the ratio of Bax to Bcl-2, resulting in exacerbating apoptosis of IPEC-J2, and Que reduced the ratio of Bax to Bcl-2 in IPEC-J2, showing a better inhibitory effect on apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the ratio of Bax to Bcl-2 is used to evaluate the degree of apoptosis. When the ratio increases, and apoptosis will be aggravated [ 57 ]. The results revealed that H 2 O 2 increased the ratio of Bax to Bcl-2, resulting in exacerbating apoptosis of IPEC-J2, and Que reduced the ratio of Bax to Bcl-2 in IPEC-J2, showing a better inhibitory effect on apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a chronic cerebral hypoperfusion model induced by bilateral common carotid artery ligation in rats, eight-week treatment of SLT significantly suppressed hypoperfusion-induced cognitive impairments, and this change is associated with reduction of activity of cholinesterase and increased acetylcholine (ACh) levels and superoxide dismutase (SOD) activity the brain tissue [ 8 ]. Our previous work also showed that SLT protected cultured human vascular endothelial cells against hydrogen peroxide-induce injury via increase in SOD activity [ 12 ]. The potential beneficial effects of SLT for VaD were demonstrated in two separate phase II randomized, double-blinded, placebo-controlled clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular protective effects of single herbal extracts and/or their isolated bioactive component on AAA have been demonstrated in a number of animal studies ( Table 1 ). However, direct evidence to support the use of complex herbal formulations for AAA is limited even though a number of complex Chinese herbal formulations, such as Si Miao Yong An (SMYA) ( 51 ), Sai Lou Tong (SLT) ( 16 ), Tong Xin Luo (TXL) capsule ( 52 ) and Huang Lian Jie Du Tang ( 53 ), have been shown to have vascular protective effects. In a head-to-head comparison study between TXL capsule (consisting of Radix ginseng , Buthus martensii , Hirudo medicinalis , Eupolyphaga seu steleophaga , Scolopendra subspinipes , Periostracum cicadae , Paeoniae rubra , Semen ziziphi spinosae , Lignum dalbergiae odoriferae , Lignum santali albi , and Borneolum syntheticum ) and simvastatin, both TXL and simvastatin at high dose showed to enhance plaque stability with similar lipid-lowering, anti-inflammatory and anti-oxidative effects in a rabbit model of atherosclerosis.…”
Section: Chm As Potential Drug Therapy For Aaamentioning
confidence: 99%
“…Many CHMs have been shown to have remarkable anti-oxidative properties ( 107 , 108 ). For instance, Sailuotong (SLT), a standardised three-herb formula combining specific dosages of Panax ginseng (Ren Shen), Ginkgo biloba (Yin Xin Ye), and Crocus sativus (Zhuang Hong Hua), has been shown to protect endothelial cell from ROS-induced apoptosis via enhancement of superoxide dismutase (SOD) activity and suppression of caspase-3 activation ( 16 ). EGb 761, a standardized extract of Ginkgo biloba is a well-known anti-oxidant ( 109 , 110 ).…”
Section: Chm As Potential Drug Therapy For Aaamentioning
confidence: 99%